I owe you one [compact disc, unabridged] : a novel - Kinsella, Sophie (Random House Audio, 2019)
When a stranger gives her an IOU for saving his computer from disaster, Fixie never imagines she will use it, until her childhood crush Ryan comes back into her life needing a job.